Effect of Planting Method on Sweet Potato Vine Dry Matter Yield - Ondabu , N.; Kenana , R.; Mwangi, J.; Irungu , K.R.G.; Changwony , K.; Kitilit , J.K.; Mugo , B. (African Journal of Education,Science and Technology (AJEST), 2014)
Sweet potato (Ipomea batatas (L) Lam) is a tropical crop mainly used for human consumption and animal feed. A farmer survey in Nakuru District revealed that sweet potato vines are potential ruminant feed. Although these vines are protein rich, there is a limited production technology to promote adoption and upscaling. The objective of this study was to develop the best planting method for fodder sweet potato. Sweet potato cultivar Wagabolige which has high pest and disease resistance was planted in KARI-Lanet. Four planting methods commonly used by farmers which included ridge, flat, valley and mound were evaluated to determine their effect on herbage yield. The experimental design used was randomized complete block design (RCBD) with three Replicates. The experiment was conducted thrice in three seasons. The valley treatment significantly (P<0.01) out yielded all the other three planting methods with 13.1kg of dry matter (DM) per plot whereas mound had the lowest yield of 10.2 kg. There were highly significant (P<0.01) differences between flat and ridge, but there was no significant (P>0.05) difference between valley and flat treatments. There were highly significant (P<0.01) differences on DM yield between seasons of harvest. The yields for the first harvest were highest with 14.5 kg DM compared to subsequent harvest with 9.9 kg DM. These results demonstrate the seasonal influence on DM yield in sweet potato vines. This information should be disseminated to farmers to stimulate the production of more herbage (vines) for their livestock.